Garmultin-A Incites Apoptosis in CB3 Cells Through miR-17-5p by Attenuating Poly (ADP-Ribose) Polymerase-1. Issue 4 (11th October 2022) - Qiu, Jianfei; Chen, Li; Yang, Jue; Varier, Krishnapriya M.; Gajendran, Babu; Yao, Yao; Liu, Wuling; Song, Jingrui; Rao, Qing; Long, Qun; Yuan, Chunmao; Hao, Xiaojiang; et al.
Background: Leukemia accounts for a large number of deaths, worldwide, every year. Treating this ailment is always a challenging job. Recently, oncogenic miRNA leading to apoptosis are highly promising targets of many natural products. In this study, Garmultin-A (GA), isolated from the bark of Garcinia multiflora, was elucidated for its anti-leukemic effect in CB3 cells. Methods: The effect of the compound on CB3 cell viability was detected by MTT assay and apoptosis by FITC Annexin V/PI and Hochest 33258 staining. The western blot analysis assessed the BAX, BCL2, cMYC, pERK, and PARP-1 protein levels. Autodock analysis predicted the ligand–protein interactions. q-RT-PCR quantified the miR-17-5p expression. Luciferase assay confirmed the interaction between PARP-1 and miR-17-5p. Results: We uncover that GA leads to apoptosis by inducing overexpression of miR-17-5p and significantly downregulate PARP-1 protein levels in CB3 cells. The overexpression of miR-17-5p promotes apoptosis, and the miR-17-5p antagomirs restore GA-triggered apoptosis. Notably, we disclose that PARP-1 is a direct target of miR-17-5p. Increased pro-apoptotic and reduced anti-apoptosis protein levels were also observed in GA-treated CB3 cells. Conclusion: These results provide critical insights that GA could induce apoptosis in CB3 cells through targeting miR-17-5p by attenuating PARP-1. Thus, GA could act as a novel therapeutic agent for erythroleukemia.